The effects of time management and effective study skills training on academic success of Filipino high school students - Lanting, Joy M. (Animo Repository, 2010)
One of the most important tasks of student athletes is to have balance between their academics and sports career. The main purpose of the study was to determine whether time management and study skills were effective tools on academic success of Filipino high school student athletes. Eighteen high school student athletes' time management and study skills were assessed using the Survey of Study Habits and Attitudes (SSHA) and underwent time management and study skill training. Pretest-posttest designed was used in the study. Data were analyzed using t-test. One sample t-test for each gender (male and female) was employed because of the researcher's observation that female participants were more participative and attentive than male participants. There is no significant difference on the pretest and posttest scores of SSHA scales except for the females' study attitude. Change in study attitude was evident among female participants mainly because they were more focused while answering the survey and more participative.